HISTORY AND EVOLUTION OF STANDARDIZED TESTING – A LITERATURE REVIEW - Kaukab, Rakhshanda; Mehrunnisa, Syeda (International Journal of Research -GRANTHAALAYAH, 2016)
This paper has been written with the intent of providing the history and evolution of the modern standardized testing while also highlighting the importance, pros and cons of standardized testing. In Pakistan, recently the higher education institution has established institute for development and implementation of standardized testing for admissions to the universities. It is for the first time that this is being introduced. Therefore, it appears in order that first the global development and need of standardized testing be researched upon and understood. This paper is an effort in combining the various sources on standardized testing in one paper.